Epileptic high-frequency oscillations occur in neonates with a high risk for seizures - Kuhnke, Nicola; Wusthoff, Courtney J.; Swarnalingam, Eroshini; Yanoussi, Mina; Jacobs, Julia (Frontiers in Neurology, 2023)
Scalp High frequency oscillations (HFO, 80-250Hz) are increasingly recognized as EEG markers of epileptic brain activity. It is, however, unclear what level of brain maturity is necessary to generate these oscillations. Many studies have reported the occurrence of scalp HFO in children with a correlation between treatment success of epileptic seizures and the reduction of HFO. More recent studies describe reliable detection of HFO on scalp EEG during the neonatal period. In the present study, continuous EEGs of 38 neonates at risk for seizures were analyzed visually for the scalp HFO using 30 minutes of quiet sleep EEG. EEGs of 14 patients were of good enough quality to analyze HFO. The average rate of HFO was 0.34 ± 0.46/min. 3.2% of HFO occurred associated with epileptic spikes. HFO were significantly more frequent in EEGs with abnormal versus normal background activity (p=0.005). Neonatal brains are capable of generating HFO. HFO could be viable biomarkers for neonates at risk of developing seizures. Our preliminary data suggest that HFOs mainly occur in those neonates who have altered background activity. Lager data sets are needed to conclude whether HFO occurrence is linked to seizure generation and this might predict the development of epilepsy.